Glaciations in South America - Poire, Daniel Gustavo; Gómez Peral, Lucia; Arrouy, Maria Julia
Neoproterozoic successions in South America are recordedin many areas of Brazil, Paraguay, Bolivia, Uruguay andArgentina. Some of these units show glaciogenic forma-tions like those represented in the Puga and Serra Azulformations in the Northern Paraguay Belt (Brazil) inagreement with their accumulation in a Snowball Earthcontext. However, in other cases, tillites or other glacio-marine deposits are absent, which may indicate a distantposition (tropical) regarding the ice cap, as occurs in theTandilia System (Argentina) related to a“Phantom glacial”context. In this contribution we show the comparisonbetween direct and indirect evidence of glaciations in theNeoproterozoic successions of South America. The Pugaand Serra Azul formations in the Paraguay Belt and SierrasBayas Group in the Río de la Plata Craton have beenchosen to describe the“Snowball Earth”and“Phantomglacial”models, respectively. By means of multiproxyanalysis it is also possible to indicate changes in paleocli-mate conditions in both cases. The presence of tillites isconsidered to be direct evidence of the extreme climaticconditions during deposition during a glaciation. Mean-while, more subtle evidence such as regional unconformi-ties related to drastic sea level changes, trends ind13C,events of phosphogenesis, constitute, among others, thetools to indicate the influence of Neoproterozoic globalglaciations during the deposition of the sedimentary units. Fil: Poire, Daniel Gustavo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigaciones Geológicas. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Investigaciones Geológicas; Argentina Fil: Gómez Peral, Lucia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigaciones Geológicas. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Investigaciones Geológicas; Argentina Fil: ...